2008
DOI: 10.1007/s00267-008-9163-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Conservation and Development at the National Marine Park of Alonissos, Northern Sporades, Greece: Perception and Practice

Abstract: Available information on the socioeconomic implications of marine protected areas (MPAs) for the socioculturally diverse Mediterranean region is scant. The National Marine Park of Alonissos, Northern Sporades (NMPANS), Greece was established in 1992 as a foundation for the conservation of the endangered Mediterranean monk seal Monachus monachus. The evolution of the degree of acceptance of and satisfaction from the NMPANS by involved stakeholder groups (fishermen, tourism operators, hoteliers and owners of roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
0
40
0
1
Order By: Relevance
“…Three articles also reported on fishers' perceptions of costs and benefits of MPAs (Gelcich et al, 2005(Gelcich et al, , 2009McClanahan et al, 2008). Five articles reported information on fishers' attitudes regarding empowerment and participation in the management and decision-making processes (Suman et al, 1999;Himes, 2003;Stump & Kriwoken, 2006;Oikonomou & Dikou, 2008;Gelcich et al, 2009). Three studies reported on fishers' perceptions regarding conflicts between different resource-users (Blyth et al, 2002;Dimech et al, 2009;Suuronen et al, 2010).…”
Section: Governance Issues Related To Mpasmentioning
confidence: 95%
See 3 more Smart Citations
“…Three articles also reported on fishers' perceptions of costs and benefits of MPAs (Gelcich et al, 2005(Gelcich et al, , 2009McClanahan et al, 2008). Five articles reported information on fishers' attitudes regarding empowerment and participation in the management and decision-making processes (Suman et al, 1999;Himes, 2003;Stump & Kriwoken, 2006;Oikonomou & Dikou, 2008;Gelcich et al, 2009). Three studies reported on fishers' perceptions regarding conflicts between different resource-users (Blyth et al, 2002;Dimech et al, 2009;Suuronen et al, 2010).…”
Section: Governance Issues Related To Mpasmentioning
confidence: 95%
“…Information on this topic was collected in 14 out of the 16 studies, and the studies assessed fishers' perceptions on a wide array of issues related to governance. Ten articles reported on fishers' attitudes, perceptions or opinions regarding MPAs as management tools (Blyth et al, 2002;Mangi & Austen, 2008) and on the acceptance and effectiveness of these management measures (Suman et al, 1999;Himes, 2003;Gelcich et al, 2005;McClanahan et al, 2005McClanahan et al, , 2008Jones, 2008;Oikonomou & Dikou, 2008;Suuronen et al, 2010). Three articles also reported on fishers' perceptions of costs and benefits of MPAs (Gelcich et al, 2005(Gelcich et al, , 2009McClanahan et al, 2008).…”
Section: Governance Issues Related To Mpasmentioning
confidence: 96%
See 2 more Smart Citations
“…The location ALO is within the National Marine Park of Alonnisos North Sporades (NMPANS), established 14 years ago for the protection of the endangered Mediterranean monk seal Monachus monachus. Within NM-PANS the controlled use of resources is permitted and fishermen express strong dissatisfaction since fishing grounds have shrunk due to containment measures (Oikonomou & Dikou, 2008). Illegal fishing is considered quite extended (Table 1).…”
Section: Methodsmentioning
confidence: 99%